Analysis of Work Accidents and Work Accident Benefits in 2016 in East Java - Rinda Ardila Megasari (Universitas Airlangga, 2022)
Introduction: According to data from the Ministry of Manpower of the Republic of Indonesia in 2016, it shows that there were 16,880 work accidents that occurred in East Java, which were classified as an OHS emergency. This study aims to analyze the incidence of work accidents and the amount of work accident insurance benefits received by the participants of Employment Insurance and Social Security in East Java Province. Methods: This study used non-reactive research and secondary data, namely gender, age, accident location, time of accident, number of work accidents and data on the number of benefits received by the participants of Employment Insurance and Social Security in East Java in 2016. The number of samples was 4,700 respondents. The analysis was conducted by comparing the number of work accidents with the amount of benefits received by workers participating in the Employment Insurance and Social Security. Results: The results showed that based on gender, the highest occupational accident cases occurred in male workers (80%), most of the occupational accident cases occurred at the age <25 years old- 35 years old (56%), the location of the accident mostly occurred at work locations (70%), and most of the accidents occurred at 06.01-12.00 (46%). Conclusion: The case of work accidents in 2016 in East Java when compared to the number of work safety benefit recipients was 0.77% and the ratio of the number of work accident cases with the highest work safety benefit amount was in permanent total disability (1: 4,800,000).